Pengaruh Kelelahan Kerja, Kemacetan Karir, Kepuasan Kerja, dan Keterlibatan Karyawan terhadap Turnover Intention pada Kayawan PT. Maha Sentral Sejati - Syaefulloh, Rahmat; Nindya Aryandha, Pradita; Kasnowo, Kasnowo; Imam Basri, Anindita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
This study aims to examine the influence of Job Burnout, Career Plateu, Job Satisfaction, and Employee Engagement on Turnover Intention at PT. Maha Sentral Sejati. The population in this study includes all employees of PT Maha Sentral Sejati, consisting of 10 office employees and 40 marketing employees, making a total population of 50 individuals. The sampling technique used is non-probability sampling by applying specific characteristics, also known as purposive sampling. The sample of this study was 50 people. The questionnaire was distributed using WhatsApp social media, and processed using SPSS tools. The results of the study showed that (1) work fatigue has a positive and significant effect on turnover intention. (2) career stagnation has a positive and significant effect on turnover intention. (3) job satisfaction has a positive and significant effect on turnover intention. (4) employee engagement has a positive and significant effect on turnover intention.